2016
DOI: 10.1039/c6nj00517a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical characteristics of 2,3,12,13-tetraalkylbacteriochlorins

Abstract: Bacteriochlorins absorb strongly in the near-infrared spectral region and hence are of great interest across the field of photochemistry. The established de novo self-condensation of a dihydrodipyrrinacetal has afforded stable bacteriochlorins bearing a variety of b-pyrrolic substituents, but the route was incompatible with the presence of two alkyl groups. The lacuna stemmed from the instability of the dialkyl-substituted dihydrodipyrrin-acetal. Here, two dihydrodipyrrin-carboxaldehydes, each bearing a tert-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…A wide variety of dihydrodipyrrin-carboxaldehydes are now known and could be examined for reaction with an aryl Grignard reagent. Dihydrodipyrrin–carboxaldehyde 5 bears two β-methyl groups and a stabilizing α-ester unit [ 36 ]. Treatment of 5 with commercially available p -tolylmagnesium bromide gave the target dihydrodipyrrin–carbinol 6a in 56% yield ( Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A wide variety of dihydrodipyrrin-carboxaldehydes are now known and could be examined for reaction with an aryl Grignard reagent. Dihydrodipyrrin–carboxaldehyde 5 bears two β-methyl groups and a stabilizing α-ester unit [ 36 ]. Treatment of 5 with commercially available p -tolylmagnesium bromide gave the target dihydrodipyrrin–carbinol 6a in 56% yield ( Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The acetal unit has been the dominant group installed at the dihydrodipyrrin 1-position, and also has been the object of the most extensive refinement, yet other groups also have been explored [ 33 , 36 ]. Here, substitution of the 1-methyl group with both an aryl group and a hydroxy or acetoxy substituent gave rise to the corresponding bacteriochlorin, which is attributed to the stabilization imparted by the aryl group, with p -anisyl superior to p -tolyl for obvious electronic reasons ( Scheme 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Separation of trivalent actinides from trivalent lanthanides is a challenging goal as the physicochemical properties of the two groups of elements are very similar. 11 This renders their chemical separation a challenging task, particularly given the high radioactivity of the waste necessitating the need for remote handling. Fortunately, previous studies have shown that separation of the minor actinides from lanthanides can be achieved by the SANEX solvent extraction process (Selective ActiNide EXtraction) using soft N-donor ligands containing the 1,2,4-triazine moiety (Figure 1).…”
mentioning
confidence: 99%